Overexpression of Extracellular Superoxide Dismutase 3 Inhibits Cancer Cell Growth and Migration in Colorectal Cancer - Wang, Donghua; Chen, Manyu; Tao, Zhenggui; Du, Jinghu; Tian, Kui; Chen, Zhen; Yu, Bo; Chen, Yu; Lv, Long (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Incidence of colorectal cancer is rapidly increasing worldwide. Extracellular superoxide dismutase (EcSOD; SOD3) is an antioxidant enzyme. However, SOD3 roles in colorectal cancer progression remain uncertain. Materials and Methods: Superoxide dismutase 3 expression was evaluated, and we analyzed clinical relevance of SOD3 expression in colorectal cancer. Subsequently, SOD3 roles in colorectal cancer progression were detected by gain of function experiments. Changes in subcutaneous tumor and liver nodule size after SOD3 overexpression were examined in nude mice. The expression of proliferation marker Ki67 was assessed by immunohistochemical staining. Results: Supperoxide dismutase 3 was downregulated in colorectal cancer (P < .01). Downregulation of SOD3 was correlated with unfavorable outcomes (P < .05). Superoxide dismutase 3 upregulation limited the proliferative (P < .05), migrative (P < .01) and invasive actions of colorectal cancer cells (P < .01) by suppressing epithelial–mesenchymal transition. Moreover, SOD3 overexpression reduced Ki67 expression (P < .01) and blocked tumor growth (P < .01) and liver metastasis (P < .001) in mouse tumor model. Conclusion: Superoxide dismutase 3 upregulation attenuates tumor growth and liver metastasis in colorectal cancer, suggesting that SOD3 has potential diagnostic and prognostic values regarding colorectal cancer treatment. Cite this article as: Wang D, Chen M, Tao Z, et al. Overexpression of extracellular superoxide dismutase 3 inhibits cancer cell growth and migration in colorectal cancer. Turk J Gastroenterol. 2024;35(6):465-474.